Morphological and biomechanical effects of annulus fibrosus injury and repair in an ovine cervical model. Issue 1 (21st December 2019) - Long, Rose G.; Ferguson, Stephen J.; Benneker, Lorin M.; Sakai, Daisuke; Li, Zhen; Pandit, Abhay; Grijpma, Dirk W.; Eglin, David; Zeiter, Stephan; Schmid, Tanja; Eberli, Ursula; Nehrbass, Dirk; et al.
Abstract: Tissue engineering repair of annulus fibrosus (AF) defects has the potential to prevent disability and pain from intervertebral disc (IVD) herniation and its progression to degeneration. Clinical translation of AF repair methods requires assessment in long‐term large animal models. An ovine AF injury model was developed using cervical spinal levels and a biopsy‐type AF defect to assess composite tissue engineering repair in 1‐month and 12‐month studies. The repair used a fibrin hydrogel crosslinked with genipin (FibGen) to seal defects, poly(trimethylene carbonate) (PTMC) scaffolds to replace lost AF tissue, and polyurethane membranes to prevent herniation. In the 1‐month study, PTMC scaffolds sealed with FibGen herniated with polyurethane membranes. When applied alone, FibGen integrated with the surrounding AF tissue without herniation, showing promise for long‐term studies. The 12‐month long‐term study used only FibGen which showed fibrous healing, biomaterial resorption and no obvious hydrogel‐related complications. However, the 2 mm biopsy punch injury condition also exhibited fibrotic healing at 12 months. Both untreated and FibGen treated groups showed equivalency with no detectable differences in histological grades of proteoglycans, cellular morphology, IVD structure and blood vessel formation, biomechanical properties including torque range and axial range of motion, Pfirrmann grade, IVD height, and quantitative scores of vertebral body changes from clinical computed tomography. The biopsy‐type injury caused endplate defects with a high prevalence of osteophytes in all groups and no nucleus herniation, indicating that the biopsy‐type injury requires further refinement, such as reduction to a slit‐type defect that could penetrate the full depth of the AF without damaging the endplate. Results demonstrate translational feasibility of FibGen for AF repair to seal AF defects, although future study with a more refined injury model is required to validate the efficacy of FibGen before translation.